Agent-Based Distributed Energy Management - Li, Jiaming; Poulton, Geoff; James, Geoff (AI 2007: Advances in Artificial Intelligence, 2007)
This paper describes our research in technologies for the management and control of distributed energy resources. An agent-based management and control system is being developed to enable large-scale deployment of distributed energy resources. Local intelligent agents will allow consumers who are connected at low levels in the distribution network to manage their energy requirements and participate in coordination responses to network stimuli. Such responses can be used to reduce the volatility of wholesale electricity prices and assist constrained networks during summer and winter demand peaks. The management and control of very large numbers of distributed energy resources to create aggregated quantities of power can be used to improve the efficiency of the electricity network and market. In our system, the coordination of energy resources is decentralized. Energy resources coordinate each other to realize efficient autonomous matching of supply and demand in large power distribution networks. The information exchange is through indirect (or stigmergic) communications between resource agents and a broker agent. The coordination mechanism is asynchronous and adapts to change in an unsupervised manner, making it intrinsically scalable and robust.